Six Guatemala municipalities benefit from a community-based climate risk and food security surveillance system, directly reaching 7,500 households - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
CCAFS scientists supported the Guatemalan government in the co-design and implementation of a hybrid community-based climate risk and food security surveillance system. The system supports the generation of information in 6 municipalities in the Dry Corridor and is scaled to other regions. The information is shared in the municipal food security councils that integrate main public sector decision-makers regarding food security. The information benefits decision-making as it helps to make more effective, timely and targeted decisions on food-security interventions. Acute food insecurity in the Guatemalan Dry Corridor is highly related to climate change and increased periods of drought. Within the Chiquimula department, the system was implemented in 6 municipalities, in each municipality monitoring 6 communities. The sampling is representative for 58 000 families in the Chiquimula department, whereas 7500 families benefit directly from the system in the department as they form part of the monitored and attended communities.